Biofumigation with species of the Brassicaceae family: a review - Santos,Carlos Antônio dos (2021)
ABSTRACT: Biofumigation involves the release of volatile biocidal compounds in the soil through the incorporation of certain plants and their residues. Species of the Brassicaceae family are the most widely used plants for biofumigation. These plants contain glucosinolates, which produce compounds, such as isothiocyanates, following enzymatic hydrolysis, with scientifically proven fungicidal effects. The most commonly used brassica species belong to the genera Brassica, Raphanus, Sinapis, and Eruca. In addition to the release of compounds in the soil, complementary mechanisms, such as the supply of organic matter and nutrients, and improvement of the soil structure, also play a role in biofumigation. In the past two decades, several studies on the use of brassica residues in biofumigation have been published, showing promising results in the management of soil pathogens (fungi and oomycetes, nematodes, bacteria, and protozoa), weed seeds, and insects. Usage of new biofumigation compounds has also been validated in recent years, including the development of patented technological products such as liquid formulations and pellets. The objective of this article was to review these new developments, beginning with concepts related to biofumigation, and to discuss the mechanisms of action of compounds involving brassica species and the recommendations on usage. Promising examples of the use of this technique are also presented, further detailing the advances in basic and applied knowledge on the subject.